The future of sleep apnea management: we can either ride the bus or drive it - Pittman, Stephen D.; Chase, Barry; Gottlieb, Daniel J.; Hwang, Dennis; Kirsch, Douglas B.; Shah, Neomi A.; Sterling, Kimberly L.; Thornton, Keith; Barnes, Teresa R.; Tosi, John; Carden, Kelly A.; Bogan, Richard K.; et al. (Frontiers in Sleep, 2024)
This consensus conference report summarizes discussions on sleep apnea care and management. Our goal is to simplify the journey to optimize success for individuals at risk of obstructive sleep apnea and to facilitate diagnostics, monitoring and communication among the entire healthcare team including patients, primary care physicians, sleep specialists, sleep dentists and other key providers. The statement identifies five key problems or unmet needs and contemplates four potential future directions.